To acquire or not to acquire? Duration of due diligence in technology acquisitions - Huma Javaid; Xavier Castaner; Panos Desyllas; Orietta Marsili (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2023)
Based on information economics and organizational learning literatures, we investigate how information asymmetry and uncertainty regarding the value of technological resources of target firms influence the due diligence process after an acquisition announcement is made by the acquirer. We study how information asymmetry between the acquirer and target firm captured by the technological distance between the two firms' patent portfolio extends the due diligence process. Additionally, we study how uncertainty about target firms' technological resources explained by the pending patent applications of target firms tends to prolong the duration of due diligence. Further, we argue that business similarity reduces information asymmetry between the acquirer and target firm and shortens the duration of due diligence. We test the predictions on a sample of acquisitions of privately held technology firms in the UK and find a significantly positive effect of targets' pending patent applications on due diligence duration that is amplified by technological distance but reduced by business similarity. The findings of the study contribute to the M&A literature that higher information asymmetry and uncertainty lengthen the due diligence process of the acquirers when evaluating prospective target firms.
Keywords: 330; Mergers and Acquisitions (M&A); Due diligence; Information asymmetry; Uncertainty